Comparison of Drip‐and‐Ship Versus Mothership Delivery Models of Mechanical Thrombectomy Delivery - Lucio D'Anna; Tsering Dolkar; Orsolya Vittay; Luke Dixon; Matteo Foschi; Michele Russo; Viva Levee; Paul Bentley; Zoe Brown; Charles Hall; Omid Halse; Sohaa Jamil; et al. (Stroke: Vascular and Interventional Neurology, 2023)
Background It remains uncertain whether the drip‐and‐ship (DS) strategy (transport to the nearest primary stroke centers) or the mothership (MS) model (direct transportation to the comprehensive stroke center) is the organizational stroke model associated with the best functional outcome in acute stroke patients with large vessel occlusion. In this study, we compared the periprocedural complications and outcomes at 90 days of acute stroke patients with large vessel occlusion of the anterior circulation directly admitted to our comprehensive stroke center compared to those referred from primary stroke centers treated with mechanical thrombectomy. Methods This is a single‐center prospective observational study where patients with DS and MS were compared regarding the disability at 90 days, as assessed by applying the modified Rankin scale, the rate of successful reperfusion, and the rate of immediate complications postprocedure. Results Of 579 patients, 216 (37.30%) were MS, and 363 (62.7%) were DS. There was no difference regarding the modified Rankin scale at 3 months between the MS (36.4%) and DS (39.3%) groups of patients treated with mechanical thrombectomy (P=0.362). There was no significant difference regarding the National Institutes of Health Stroke Scale at 24 hours, mortality at 90 days, and rate of successful recanalization postprocedure between the 2 groups. DS was associated with an increased risk of hemorrhagic transformation and symptomatic intracranial hemorrhage (odds ratio, 5.414 [95% CI, 1.572–18.644]; P=0.007). Conclusion Our single‐center study showed no difference in terms of functional independence between the DS and MS organizational paradigm. DS was associated with an increased risk of hemorrhagic transformation and symptomatic intracranial hemorrhage.